2007
DOI: 10.1103/physrevb.75.224115
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure dependent ferroelectric phase transition in lead titanate

Abstract: Ti K edge x-ray absorption near-edge structure (XANES) measurements across the pressure induced ferroelectric (FE)-paraeletric (PE) phase transition in PbTiO 3 a prototypical ferroelectric perovskite, are reported for the first time. A quantitative analysis of the XANES allows us to obtain the relative local displacement, directly related to the local electric polarization, of Ti and Pb atoms under pressure. In particular, we found that above the critical pressure, in the so-called cubic-paraelectric phase, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…14͒ or no shift. 15 Additionally, although the Zr shift is found to be both temperature and composition independent, 14,16 the Ti shifts appear to have an orderdisorder component as a function of temperature 17 and pressure 18 which was found to be quite unusual for these ferroelectric displacive-type transitions. 19 This paper provides the evidence of the ferroelectric character of the Zratoms in PZT in the P-T space.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…14͒ or no shift. 15 Additionally, although the Zr shift is found to be both temperature and composition independent, 14,16 the Ti shifts appear to have an orderdisorder component as a function of temperature 17 and pressure 18 which was found to be quite unusual for these ferroelectric displacive-type transitions. 19 This paper provides the evidence of the ferroelectric character of the Zratoms in PZT in the P-T space.…”
Section: Introductionmentioning
confidence: 90%
“…2 appears at pressures well above P C suggesting an order-disorder nature of the transition, as it has already been reported for Ti shifts in P-T space. 17,18 It is worth to stress that besides the displacement of Zr from the offset position to the centrosymmetric position of 0.06 Å, Let us now discuss about the XANES part of the spectra. The p-d peak, linked to the dipole transition, is expected to disappear at the ferroelectric-paraelectric transition as in PbTiO 3 .…”
mentioning
confidence: 99%
“…With increasing demand for smarter ceramics, pressure dependent studies in some of these PbTiO 3 based ceramics have attained significance [24][25][26][27]. These investigations have not only provided the fundamental insight towards the pressure dependent phase transitions but have also increased the applicability of such ceramics [28][29][30][31]. One of the above mentioned ceramics viz., Pb 1-x Ca x TiO 3 has become subject for careful studies in recent times [17,18,21,32].…”
Section: Introductionmentioning
confidence: 97%
“…These spectroscopic techniques enable the investigation of pressure-induced changes in the local atomic structure, electronic structure and magnetic states of both the crystalline and the non-crystalline materials. After the development of perforated diamond anvils in order to reduce the X-ray absorption itself (Dadashev et al, 2001), the coverage of X-ray absorption experiments under high pressure extends to lower energies; highpressure research at the Ce L 3 -edge (5.723 keV) (Itié et al, 2005;Rueff et al, 2011) and Ti K-edge (4.966 keV) (Itié et al, 2006;Jaouen et al, 2007) have been reported.…”
Section: Introductionmentioning
confidence: 99%